Quantitative Methods for Studying Design Protocols - Kan, Jeff WT.; Gero, John S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2017)
This book is aimed at researchers and students who would like to engage in and deepen their understanding of design cognition research. The book presents new approaches for analyzing design thinking and proposes methods of measuring design processes. These methods seek to quantify design issues and design processes that are defined based on notions from the Function-Behavior-Structure (FBS) design ontology and from linkography. A linkograph is a network of linked design moves or segments. FBS ontology concepts have been used in both design theory and design thinking research and have yielded numerous results. Linkography is one of the most influential and elegant design cognition research methods. In this book Kan and Gero provide novel and state-of-the-art methods of analyzing design protocols that offer insights into design cognition by integrating segmentation with linkography by assigning FBS-based codes to design moves or segments and treating links as FBS transformation processes. They propose and test information entropy as a means to capture the information carried by a linkograph and correlate it with the design outcomes.
Preface -- 1 Introduction -- 2 Background -- 3 Theoretical Framework -- 4 Ontologically-Based Studies of Design Protocols -- 5 Pilot Study of Statistical and Entropic description of linkographs -- 6 Entropic Measurement and Design Outcome -- 7 Conclusions -- References -- Appendix A.
Keywords: Engineering design; Engineering Design